ANALISIS DAMPAK KENAIKAN HARGA KEBUTUHAN POKOK TERHADAP PERUBAHAN POLA KONSUMSI MASYARAKAT INDONESIA PADA TAHUN 2025 - Joys Octaviyani Sitohang; Timotea Lenta Sitinjak; Muhammad Habib Syakier; Hotmauli Gultom; Dede Ruslan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze entrepreneurship and leadership strategies in the This study aims to analyze the impact of rising basic commodity prices on changes in the consumption patterns of Indonesian society in 2025. The study employed a quantitative method with a descriptive approach using secondary data obtained from Statistics Indonesia (BPS), scientific journals, and related literature sources. The results indicate that the increase in the prices of basic necessities such as rice, red chili, cooking oil, sugar, and eggs has significantly affected the consumption patterns of Indonesian households. People tend to prioritize primary needs over secondary and tertiary needs. In addition, households have implemented various saving strategies, such as reducing non-primary consumption, choosing cheaper substitute goods, reducing shopping frequency, and utilizing savings to meet daily needs. High inflation in the food, beverage, and tobacco sectors has also increased the proportion of household expenditure allocated to food consumption. This study concludes that the rising prices of basic necessities have had a significant impact on the purchasing power and welfare of Indonesian society in 2025.